Case report: A rare case of intragastric metastasis after liver transplantation for liver cancer - Xue, Youfeng; Shi, Baojie; Zhong, Jianfa; Wang, Guimei; Wang, Jie; An, Wenbin; Qian, Yunyun; Su, Zhaojie; Peng, Zhihai; Li, Hao (Frontiers in Oncology, 2024)
A 13-year-old boy was admitted to Xiang’an Hospital of Xiamen University due to HBV-related liver cancer. Intrahepatic metastasis was considered to occur by CT scan. A gastroscope revealed esophagogastric variceal bleeding, and later, the patient underwent a successful liver transplantation. Fourteen months posttransplant, chest CT indicated lung metastasis, and the patient underwent thoracoscopic radical resection of lung cancer. Twenty-one months posttransplant, gastroscopy revealed a gastric fundus tumor growing into the gastric cavity. Proximal gastrectomy was performed, and pathology indicated moderately to poorly differentiated carcinoma without invasion of serosa, suggesting the first study to report HCC metastasis to the stomach lumen without invasion of serosa after LT. Currently, the alpha-fetoprotein (AFP) level of the patient has dropped below normal.